2010
DOI: 10.4269/ajtmh.2010.10-0198
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks in Travelers to South Africa: The GeoSentinel Experience and Implications for the 2010 FIFA World Cup

Abstract: Abstract. Using the GeoSentinel database, an analysis of ill patients returning from throughout sub-Saharan Africa over a 13-year period was performed. Systemic febrile illness, dermatologic, and acute diarrheal illness were the most common syndromic groupings, whereas spotted fever group rickettsiosis was the most common individual diagnosis for travelers to South Africa. In contrast to the rest of sub-Saharan Africa, only six cases of malaria were documented in South Africa travelers. Vaccine-preventable dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…ATBF was the second most frequently identified etiology, after malaria, among travelers returning from sub-Saharan Africa (118). This finding was confirmed subsequently by other studies (383,386). The risk factors for ATBF in travel are male gender, higher age, travel for tourism, and travel during the late summer months in southern Africa (March to May) (385,387).…”
Section: Sub-saharan Africasupporting
confidence: 78%
“…ATBF was the second most frequently identified etiology, after malaria, among travelers returning from sub-Saharan Africa (118). This finding was confirmed subsequently by other studies (383,386). The risk factors for ATBF in travel are male gender, higher age, travel for tourism, and travel during the late summer months in southern Africa (March to May) (385,387).…”
Section: Sub-saharan Africasupporting
confidence: 78%
“…An early 2008 study of aggregated data from ill travelers to China in the previous decade allowed provision of evidencebased recommendations for the 2008 Beijing Olympics [11]. A similar study was published in 2010 prior to the FIFA World Cup in South Africa [12].…”
Section: Provider-based Surveillance To Inform Travelers Before Mass mentioning
confidence: 91%
“…2.3 Output of significant events is visually geolocated using a Google Maps platform. HealthMap heralds a generation of surveillance technology that complements existing travelers' health surveillance systems [12,13].…”
Section: Analysis Of Morbidity and Estimating Risk By Destinationmentioning
confidence: 99%
“…Most of these cases of illness (54.5%) were due to spotted fever group rickettsiosis. 3 The risk of acquiring rickettsiosis increases among travellers visiting game parks, with an incidence of African tick bite fever (Rickettsia africae) among short-term safari tourists of 4.0%-5.3%. 4 Measles has rarely been reported in travellers returning from South Africa, 2 but the country is in the midst of a measles epidemic, with 17 354 confirmed cases between January 2009 and 12 August 2010.…”
Section: World Cup Fevermentioning
confidence: 99%
“…Recent data from the GeoSentinal surveillance network showed that a systemic febrile illness was the most common presenting syndrome among travellers returning from South Africa. Most of these cases of illness (54.5%) were due to spotted fever group rickettsiosis 3 . The risk of acquiring rickettsiosis increases among travellers visiting game parks, with an incidence of African tick bite fever ( Rickettsia africae ) among short‐term safari tourists of 4.0%–5.3% 4 …”
mentioning
confidence: 99%